Muscone Ameliorates High-Altitude Hypoxia Gastrointestinal Stress via Modulation of Lactobacillus Murinus and Mitochondrial Metabolism - Zeng J; Yin X; Pang Y; Zhang J; Xie C; Chen S; Zhang L; Li X; Pan Y; An J (Journal of Inflammation Research)
Jin Zeng,1,* Xinxin Yin,1,* Yidan Pang,1 Jinglei Zhang,1 Changpeng Xie,1 Siai Chen,1 Liping Zhang,1 Xuejing Li,1 YuanMing Pan,2 Juan An1 1Department of Basic Medical Sciences, Qinghai University Medical College, Xi’ning, Qinghai Province, People’s Republic of China; 2Cancer Research Center, Beijing Chest Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juan An, Department of Basic Medical Sciences, Qinghai University Medical College, Xi’ning, Qinghai Province, People’s Republic of China, Email anjuan@qhu.edu.cn YuanMing Pan, Cancer Research Center, Beijing Chest Hospital, Capital Medical University, Beijing, People’s Republic of China, Email peterfpan2020@mail.ccmu.edu.cnPurpose: This study is to investigate the previously unexamined mechanism through which muscone alleviates acute high-altitude gastrointestinal stress. Specifically, it focuses on the modulation of gut microbiota, emphasizing its role in promoting the abundance of Lactobacillus murinus and optimizing mitochondrial metabolic pathways.Patients and Methods: A high-altitude hypoxia model mouse treated with muscone was established to assess routine blood indices, inflammatory factors, and inflammatory cell counts. Additionally, alterations in intestinal flora were analyzed using macrogenomics. To further investigate the relationship between muscone’s mechanism of action and intestinal flora, the ABX hypoxia mice model was employed, alongside in vitro experiments to evaluate muscone’s effect on the growth of Lactobacillus murinus. The ameliorative effects of Lactobacillus murinus on acute gastrointestinal stress induced by high-altitude conditions were validated through various methods, such as HE staining, immunohistochemistry, transmission electron microscopy, ELISA, and flow cytometry. Furthermore, the underlying mechanism was explored through transcriptomics and qPCR.Results: Muscone markedly alleviated hypoxia-induced inflammation improved hematological parameters, and reshaped gut microbiota composition, with a notable increase in the abundance of Lactobacillus murinus. In vitro, muscone directly stimulated the proliferation of Lactobacillus murinus. However, the protective effects of muscone were significantly diminished in ABX-treated mice, highlighting the critical role of the gut microbiota. Supplementation with Lactobacillus murinus alone effectively reduced serum inflammatory cytokines, alleviated intestinal oxidative stress, and restored mucosal integrity. Transcriptomic analysis and RT-qPCR findings suggest that these effects may be linked to the mitochondrial metabolic pathway.Conclusion: Muscone may alleviate acute high-altitude gastrointestinal stress by enhancing the abundance of Lactobacillus murinus within the intestinal tract. Its mechanism of action appears to be associated with mitochondrial metabolic pathways. Keywords: high-altitude hypoxia, oxidative stress, muscone, gut microbiota, lactobacillus murinus